Monitoring Organic Reactions by Micellar Electrokinetic Chromatography. (4th March 2012) - Yang, Chun; Chang, Chunyang; Wang, Jun; Qu, Qishu; Hu, Xiaoya; Wang, Yang
Abstract : A method was established to monitor organic reactions by micellar capillary electrokinetic chromatography (MEKC). After optimizing conditions such as the composition of the solvents, the surfactant, and the apparent pH (pH*) of the system, the method was utilized to analyze the reaction of glycidyl methacrylate (GMA) and allyl amine. The main products were identified in the electropherograms. The reaction procedure was monitored in real time. This method was found to have common applicability, being able to separate and detect nonaqueous soluble, nonionic, and low-UV-Vis absorbance compounds. It provides a rapid and low-cost way to understand organic reactions and to direct synthesis works.